2007
DOI: 10.1093/eurheartj/ehm480
|View full text |Cite
|
Sign up to set email alerts
|

Renal dysfunction, as measured by the modification of diet in renal disease equations, and outcome in patients with advanced heart failure

Abstract: NT-proBNP appears superior to GFR estimated by MDRD in patients with advanced CHF. Moreover, NT-proBNP was able to identify patients with a poor prognosis whose GFR was already low.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…Thus, in the study of Tsutamoto et al (6), HF patients with estimated GFR Ͻ40 ml/min and the highest BNP levels did indeed have higher median LV end-diastolic pressure compared with those with better preserved GFR. Such patients with presumed "cardiorenal syndrome" (26) may also have higher NP levels arising from advanced heart disease, greater preload, and multiple other comorbidities (27,28). Falsely low estimated GFR caused by poor renal perfusion or diuretic use in acute HF further complicate the relationship with NPs (5).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the study of Tsutamoto et al (6), HF patients with estimated GFR Ͻ40 ml/min and the highest BNP levels did indeed have higher median LV end-diastolic pressure compared with those with better preserved GFR. Such patients with presumed "cardiorenal syndrome" (26) may also have higher NP levels arising from advanced heart disease, greater preload, and multiple other comorbidities (27,28). Falsely low estimated GFR caused by poor renal perfusion or diuretic use in acute HF further complicate the relationship with NPs (5).…”
Section: Discussionmentioning
confidence: 99%
“…It is often quoted as a barometer of renal impairment, but it is actually a poor indicator of renal function. Therefore, estimation of the glomerular filtration rate (eGFR) is preferred for the accurate assessment of renal function 4,10 . The eGFR was determined by the abbreviated Modification of Diet in Renal Disease (MDRD) formula and patients were categorized using the Kidney Disease Outcomes Quality Initiative (K/DOQI) classification system 14 .…”
Section: Methodsmentioning
confidence: 99%
“…The eGFR was determined by the abbreviated Modification of Diet in Renal Disease (MDRD) formula and patients were categorized using the Kidney Disease Outcomes Quality Initiative (K/DOQI) classification system 14 . The abbreviated MDRD formula provides valid estimation of glomerular filtration rate (GFR) and according to recent findings it is superior to the CockcroftGault formula 4,[15][16][17][18] . According to the World Health Organization (WHO) anemia is defined as hemoglobin (Hb) concentration < 13.0 g/dL in men and < 12.0 g/dL in women 19 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gardner et al reported that N-terminal prohormone brain natriuretic peptide (NT-proBNP) was a better prognostic marker than GFR from MDRD, among patients with advanced chronic heart failure. 19 Scrutinio et al 20 studied a population with normal serum creatinine and also demonstrated that the CG equation was better than MDRD for predicting heart failure-associated outcomes. The question of whether the greater sensitivity of MDRD for classifying advanced heart failure patients with renal failure reflects progressive decline in renal function or greater mortality among this population after heart transplantation remains to be addressed.…”
mentioning
confidence: 99%